Complex evaluation of contracts for construction - Podvezko, Valentinas; Mitkus, Sigitas; Trinkūnienė, Eva (Journal of Civil Engineering and Management, 2010)
The effectiveness of construction processes largely depends on the effective contract preparation. To draw an effective contract for construction, the methods of assessment and comparison of these types of contract should be developed. In recent years, multicriteria methods have been widely used for evaluating various complex phenomena. The development of construction evaluation methods requires the analysis of construction technology and organization, as well as economic factors and legal aspects of contracting in construction. In the present investigation, the criteria describing contracts for construction from various perspectives are determined based on the estimates elicited from experts. The weights of nine criteria used in complex evaluation of construction contracts are determined based on the use of the AHP method. The consistency of expert estimates is also assessed. Using multicriteria evaluation methods, construction contracts are compared and the best alternative is determined. First Published Online: 24 Jun 2011